Expression and Influence of Matrix Metalloproteinase–9/Tissue Inhibitor of Metalloproteinase–1 and Vascular Endothelial Growth Factor in Diabetic Foot Ulcers. (March 2017) - Li, Gongchi; Zou, Xinhua; Zhu, Youpeng; Zhang, Jing; Zhou, Lijun; Wang, Dan; Li, Binghui; Chen, Zhenbing
A high matrix metalloproteinase–9/tissue inhibitor of metalloproteinase–1 (MMP9/TIMP1) ratio is associated with poor ulcer healing, yet how the ratio of MMP9/TIMP1 changes in diabetic foot ulcers (DFUs) with infection and how these changes may affect wound healing remain unclear. Therefore, the objective of this investigation was to explore relationships among the MMP9/TIMP1 ratio, infection, and DFUs. After being informed of the details of this study, 32 patients signed consent forms. Skin biopsies were performed for all patients. Wound tissues were obtained from all patients with wounds, and healthy skin samples were collected from patients without wounds during orthopedic surgery. Microbial cultures were obtained using the samples from diabetic patients with wounds. All patients were divided into 4 groups according to colony-forming units (CFUs) per gram of tissue (>1 × 10 6 or <1 × 10 6 ): group A (diabetic wounds with high quantities of bacteria), group B (diabetic wounds with low quantities of bacteria), group C (diabetic patients without wounds), and group D (nondiabetic patients with wounds). In addition, the biopsies were evaluated by both reverse transcription–quantitative polymerase chain reaction and Western blotting to assess the levels of MMP9, TIMP1, and vascular endothelial growth factor (VEGF). The results show that for both mRNA and protein, expression of MMP9 (fold change 1.14 ± 0.12 vs 0.60 ± 0.08 vs 0.39±0.09 vs 0.13 ± 0.06, P < .01) decreased, whereas that of TIMP1 (1.01 ± 0.09 vs 2.86 ± 0.85 vs 4.88 ± 0.83 vs 7.29 ± 1.55, P < .01) and VEGF (1.01 ± 0.22 vs 3.55 ± 0.97 vs 5.72 ± 0.55 vs 6.92 ± 1.55, P < .01) increased from group A to group D. These results suggest that an increase in the MMP9/TIMP1 ratio in infected DFUs may induce a decrease in VEGF expression.